A referência impossível: traços do jogo musical meierholdiano - Raquel Castro de Souza (2018)
This thesis intends to investigate the traces of the musical game of Vsévolod Meierholds (1874-1940) theater in the contemporary scene, especially regarding creations and activities of theatre training carried out in Brazil, with a focus concerning the musical thought inside the scene. We start from the hypothesis that there is an incorporation of the principles and musical procedures developed by the early 20th-century Russian theatre director in the 21st-century theatre, though his legacy had been confiscated by Stalins totalitarian regime and the transmission process had been interrupted. We look, through a perspective of artistic affiliation, at the history of this legacy, searching for References, Interferences or Intersections and Resonances between Meierhold and many contemporary artists who are posterior to him. We propose, hence, an overview of the artists who consider themselves or are considered, in some aspects and in many ways, heirs or depositaries of Meierholds work in the world. In addition, we present the possibility of Impossible Reference or influence by ricochet, crossed by the idea of trace by Derrida, which allows us to consider the invisible presence of Meierholds ideas in the work of artists who developed proposals that are similar, even though they have not had direct contact with such ideas and although they have not made reference to them, revealing, thus, presupposed points of contamination that would have remained implicit and hidden. The research focuses on the analysis of the trajectory of artists from the contemporary scene who stand out when it comes to the musical game in the scene, such as the artist, director and playwright Rita Clemente and the artist, professor, and researcher Ernani Maletta. The methodological operator that sustains the approaching of these artists with Meierholds theater is the overview of principles and procedures of meierholdian musical game in the planes of acting, staging, and dramaturgy, a work of critical and descriptive intent, started in the master thesis that precedes this thesis and concluded here with the presentation of more eight principles and twenty-two procedures of musical game developed by the theatre director. This is a proposal of outlining the resources and strategies developed by Meierhold in which music works as a constructing element of the theatrical scene, tracked on the directors theoretical texts and on the reports of his scholars, which is a focus that supports the observation of the meierholdian presence in the contemporary theater.